Efektivitas Metode Talaqqi Dalam Pembelajaran Daring Tahsin Al-Qur’an Di Kelas Viii Kkq (Kelas Khusus Al-Qur’an) Smpit Asy-Syukriyyah Tangerang - Nasrulloh, Nasrulloh; Azhari, Virgiawan (Jurnal Sistem Informasi (JUSIN), 2022)
This study aims: 1) to determine the application of the talaqqi method in online learning of tahsin Al-Qur'an in class VIII SMPIT Asy-Syukriyyah Tangerang. 2) to determine the effectiveness of the application of the talaqqi method in online learning of Al-Qur'an tahsin in class VIII SMPIT Asy-Syukriyyah Tangerang. 3) to find out the inhibiting and supporting factors for the effectiveness of the application of the talaqqi method in online learning of Al-Qur'an tahsin in class VIII of SMPIT Asy-Syukriyyah Tangerang. This research was conducted using a descriptive qualitative method. Data collection techniques carried out in this study using interviews, observation and documentation. The results of this study indicate that: 1) online learning of tahsin Al-Qur'an uses the talaqqi method with the zoom meeting application to convey material and student conditioning while the whatsapp video call application for talaqqi tahsin Al-Qur'an. 2) the talaqqi method is still effectively applied in online learning even though some network problems are found, but it can still be minimized by the teacher. 3) There are several inhibiting factors in online learning such as internet network disturbances, problematic online devices and the burden of internet data package costs. In addition, there are also supporting factors in online learning such as improving internet network services by the government, student discipline and responsibility and the role of parents or guardians of students while studying at home.